Laparoscopic repair of a large umbilical hernia in a super obese woman and its outcome - Gillellamudi, Sarath Babu; Muhamad, Rehman; Kumar, B. Anil; Gogineni, Tarun; Aparna, M.; Chaitanya, V. (International Surgery Journal, 2016)
The umbilical hernia is a common surgical problem mainly encountered in the 5th and 6th decades of life. The umbilical defect is observed in more than 90% of elderly patients. It is seen mainly in obese patients, especially in women. A 52-year-old super obese woman with body mass index 53.3 kg/m2 presented with intermittent, crampy, abdominal pain. Laparoscopic umbilical hernia repair with combined herniorrhaphy and intraabdominal mesh fixation offers an efficient, safe, and effective repair for umbilical hernia in super obese women.